Adjustable tongue vane for improving the energy performance of a submersible single-channel pump for wastewater treatment - Duc-Anh Nguyen; Kexin Wu; Xiaojun Li; Gyeong Sung Kim; Jin-Hyuk Kim (Heliyon)
Single-channel pump is a type of centrifugal pump that is frequently utilized for wastewater treatment around the world, but they often operate at low flow rates with low efficiency and loud noise because the wastewater contains many impurities. In this study, an adjustable tongue vane was developed that controls the internal flow direction in the volute to increase the energy performance of a single-channel pump. Numerical simulations were conducted by using Reynolds-averaged Navier-Stokes equations and shear stress transport turbulence model to evaluate the energy loss inside the volute. In the experiment, the single-channel pump demonstrated stable operation in the waste environment. In the numerical simulation, the −10° model increased the efficiency and total head by 1.007 % and 1.242 %, respectively compared to the reference model at the best efficiency point. At low flow rates, however, the −20° model increased the efficiency and total head by up to 25.126 % and 5.604 %, respectively, while decreasing the power consumption by up to 15.533 % compared to the reference model. This improvement is attributed to the adjustable tongue vane suppressing separation flow, which reduces hydraulic losses and energy dissipation. The proposed tongue vane can be used to improve the energy performance of not only single-channel pumps but also other centrifugal turbomachinery.